2005
DOI: 10.1002/fam.901
|View full text |Cite
|
Sign up to set email alerts
|

On the ignition of fuel beds by firebrands

Abstract: SUMMARYAn experimental apparatus has been built to investigate the ignition of fuel beds as a result of impact with burning firebrands. The apparatus allowed the ignition and deposition of both single and multiple firebrands onto the target fuel bed. The moisture content of the fuel beds used was varied, and the fuels considered were pine needle beds, shredded paper beds and crevices constructed of cedar shingles. Firebrands were simulated by machining wood (Pinus ponderosa) into small disks of uniform geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
77
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 7 publications
5
77
0
Order By: Relevance
“…However, four flaming embers were not capable of igniting hardwood at 11% moisture content. Similar results are found using disk shaped embers [4,5] where flaming ignition occurred only when flaming embers are dropped. It was also observed that multiple flaming embers resulted in flaming ignition where single embers would cause no ignition.…”
Section: Spot Fire Formation: Ignition (Or Non-ignition) Of Fuel Bedssupporting
confidence: 81%
See 2 more Smart Citations
“…However, four flaming embers were not capable of igniting hardwood at 11% moisture content. Similar results are found using disk shaped embers [4,5] where flaming ignition occurred only when flaming embers are dropped. It was also observed that multiple flaming embers resulted in flaming ignition where single embers would cause no ignition.…”
Section: Spot Fire Formation: Ignition (Or Non-ignition) Of Fuel Bedssupporting
confidence: 81%
“…This complex process depends on several factors, including the size and state of the brand or particle (temperature, smoldering/ glowing, flaming), the characteristics of the fuel bed on which it lands (temperature, density, porosity, moisture content), and environmental conditions (temperature, humidity, wind velocity). Ignition of fuel beds by fire brands and heated surfaces has been studied primarily experimentally, in particular by workers at NIST [4][5][6][7]. Studies on ignition by metal particles have been reported by Rowntree and Stokes [2,3].…”
Section: Spot Fire Formation: Ignition (Or Non-ignition) Of Fuel Bedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding ornamental vegetation, Long et al (2006a) provided flammability data for horticultural beds by evaluating the effect of the type of mulch, planting composition and drought conditions on fire spread and heat release in both field and controlledenvironment conditions. Several experiments were carried out on firebrands but very few used surface fuels (Manzello et al 2006a(Manzello et al , 2006b(Manzello et al , 2007(Manzello et al , 2008(Manzello et al , 2009Ganteaume et al 2011b). …”
mentioning
confidence: 99%
“…Majority of such damages depend on source temperature and influence time. Heated up to high temperatures particles of metals and nonmetals are probable sources of high temperature at natural and technogenic fires [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%